From Knowledge Seeking to Ethical Action: The Elaboration of Taha Abdurrahman’s Philosophy to Address Student’s Information Overload - Kurniawan Dwi Saputra; Agus Himmawan Utomo (Newinera Publisher, 2026)
Rather than cultivating critical thinking, the ease of access to information in digital world, leads many students into confusion. By developing Taha Abdurrahman’s theory of subject and Linda Zagzebski’s intellectual virtues, this study aims to propose an onto-ethical approach to address students learning problem caused by information overload. Using library-based qualitative research, the authors compare and synthesis Taha’s view on subject and Zagzebski’s intellectual virtue to foster a critical-responsible digital subject. Tahaian notion of subject, which received ethico-spiritual commitment through transcendental encounter with God, is proposed as a resilient subject for information overload. Authors argue that to overcome information overload among students, the praxis of digital engagement must be altered from information seeking activity towards a responsible ethical action. To engage in digital activities is to responsibly executes certain intellectual virtues in order to do something ethical. The two-folded attributes of Tahaian subject: criticism and responsibility are essential in fostering an ethical-aware autonomous learner. Complementing this framework, this article engages through Linda Zagzebski’s theory of intellectual virtues, to tackle digital-related pedagogical problems.